Penyuluhan Hipertensi serta Pelayanan Kesehatan pada Lansia di Cengkareng Barat - Dian Mediana; Magdalena Wartono; Purnamawati Tjhin; Lie Tanu Merijanti; Kartini; Dewi Hastuty; Kurniasari; Joice Viladelphia Kalumpiu (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
Hypertension is a condition that is often found in primary health care, because the prevalence of hypertension in Indonesia is relatively high. According to RISKESDAS 2018, the prevalence of hypertension in Indonesia was 34.11%. Hypertension is a major public health problem, responsible for at least 45% of deaths from heart disease and 51% of deaths from stroke. The increasing prevalence of hypertension is caused by population growth, old age and risk factors for unhealthy dietary behavior. In addition to hypertension, through general health checks, other diseases can be found, especially degenerative diseases. In elderly it is important to carry out periodic checks because the higher the risk of degenerative diseases due to decreased the function of various organs of the body. The activities of Pengabdian Kepada Masyarakat are carried out by counseling and health care on 4th January 2023 to 42 participants aged â‰¥46 years (early elderly) at Panti Sosial Tresna Werdha Budi Mulia 4. The results of the counseling get a 43% increase in knowledge about hypertension. The results of the health care get diagnosis of 23% hypertension, 17% stroke, 17% neuralgia, 9% osteoarthritis, 9% diabetes mellitus, 9% cephalalgia, 6% gastritis, 6% dermatitis, and 4% anemia. It is hoped that this activity can run continuously to achieve better elderly health.